Pengaruh Keterlibatan Produk, Promosi, dan Persepsi Harga terhadap Loyalitas Merek Mi Instan - Imelda Ayu Setianingrum; Widyatmoko Widyatmoko (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to measure the effect of product involvement, promotion, and price perception on brand loyalty of instant noodles, with consumers of the Sedaap instant noodle brand in Kediri City as the research object. The main issue underlying this study is the high level of competition in the instant noodle industry, which requires companies to maintain consumer loyalty amid changing preferences and the abundance of alternative brands. The purpose of this study is to analyze the partial and simultaneous effects of each variable on brand loyalty. The research method employed a quantitative approach using a survey technique through a Likert-scale-based questionnaire. The research sample consisted of 150 respondents selected using probability sampling techniques. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method through SmartPLS software to test validity, reliability, and research hypotheses. The results indicate that product involvement, promotion, and price perception have a positive and significant effect on instant noodle brand loyalty. Simultaneously, these three variables also contribute significantly to shaping consumer loyalty. These findings suggest that brand loyalty is influenced not only by product quality but also by effective promotional strategies and fair price perceptions that align with the benefits perceived by consumers. The conclusion of this study emphasizes the importance of implementing integrated marketing strategies to enhance and sustain instant noodle brand loyalty in an increasingly competitive market.